ANALISA APLIKASI KONSEP TRANSFORMASI GEOMETRI PADA MOTIF BATIK LABAKO JEMBER - Saputra, Muhammad Yusuf; Sulisawati, Dwi Noviani; Murtinasari, Frida (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
This research analyzes a continually evolving culture deeply ingrained in every region of Indonesia. Jember Regency, located in East Java, boasts a rich tapestry of cultures encompassing customs, food, language, games, and more. This research uses qualitative. The research focused on batik, specifically analyzing the geometric transformations within Labako batik motifs. These transformations include translation, reflection, rotation, and dilation. A total of eight motifs were identified from four Labako batik cloths, featuring elements like water hyacinth plants, bamboo, tomato and tobacco leaves, winged beans, and coffee and cocoa fruits and leaves. This research seeks to identify geometric concepts within each motif for use as teaching materials, indirectly promoting batik preservation and supporting Labako batik craftsmen. It is also hoped that this research can be used as a reference for future studies.